Just about everybody doing the business? Explaining ‘cash-for-crash’ insurance fraud in the United Kingdom - Button, Mark (The Australian and New Zealand journal of criminology, 2017)
There is much international research on the different types of fraud committed by individuals and/or organised crime. There is, however, limited research on insurance fraud and a particular species of such fraud which has become known as ‘cash-for-crash’ fraud in the United Kingdom. In addition, there are very few published studies of fraudsters which actually draw upon interviews with them. This article bridges both of these gaps providing a focus upon ‘cash-for-crash’ fraudsters which is based upon empirical research drawn from six interviews with such offenders and a database of over 400 offenders built upon successful prosecutions of such cases in the United Kingdom. This article offers a profile of such offenders and presents insights into why and how some people might become involved in ‘cash-for-crash’ type frauds.